Anselm on THAT, THIS, and panpsychism - Mulgan, Tim ca. 20./21. Jh. (Religious studies, 2026)
This articles reimagines Anselm’s claim that God is ‘that than which a greater cannot be thought’ [Hereafter: ‘THAT’]. The article first explores a variety of Anselm-inspired of what THAT is like, and how THAT relates to whatever (if anything) is not-THAT (hereafter: ‘THIS’). THAT could be Anselm’s creator God, a polytheist pantheon, or a single undifferentiated One/Absolute/Brahman. THIS could be a single possible world or a pluriverse containing many different real possible worlds. The article defends a principle of cosmic humility. It argues that, to counter our natural tendency to over-estimate our own importance, we should pay particular attention to non-human-centred, non-anthropomorphic interpretations of THAT. Humility favours plenitude about worlds and plenitude about creatures. God (or THAT) will create many worlds that (together) contain all valuable creatures. Humility also suggests that, within this optimal pluriverse, we should not expect to find ourselves inhabiting either a world that is cosmically special or a world where we are special. The final part of the article argues that, within contemporary philosophy of mind, this commitment to cosmic humility supports panpsychism over its rivals - especially dualism and materialism. If THAT did create THIS, then we are (probably) insignificant creatures living in a panpsychist world. The article concludes with some speculations on how thinking about THAT and THIS might also influence the content of panpsychism as well as the case for panpsychism.